2018
DOI: 10.1371/journal.pone.0190626
|View full text |Cite
|
Sign up to set email alerts
|

Gluteal muscle damage leads to higher in vivo hip joint loads 3 months after total hip arthroplasty

Abstract: BackgroundTotal hip arthroplasty (THA) is in most cases improving patients´ life quality immediately after surgery. However, a closer look at these patients, especially with modern gait analysis methods, reveals also negative consequences due to the surgical approach related injury to the pelvic muscles. We hypothesized that this damage will have a negative impact on hip joint contact forces during activities of daily living (ADL).Methods10 patients undergoing THA received an instrumented hip joint implant ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 39 publications
0
18
0
2
Order By: Relevance
“…Sørensen et al [35] reported a normal hip muscle function during walking after 12 month periacetabular osteotomy, and found that joint force magnitude continued to be higher than normal, justifying this finding with the need for joint structures of a longer time to heal than muscles, with a residual pain alleviating strategy. Damm et al [36] reported a correlation between muscle atrophy, fatty degeneration and higher hip joint forces. Fatty atrophy was observed after THR contributing to functional outcome deterioration [37].…”
Section: Discussionmentioning
confidence: 98%
“…Sørensen et al [35] reported a normal hip muscle function during walking after 12 month periacetabular osteotomy, and found that joint force magnitude continued to be higher than normal, justifying this finding with the need for joint structures of a longer time to heal than muscles, with a residual pain alleviating strategy. Damm et al [36] reported a correlation between muscle atrophy, fatty degeneration and higher hip joint forces. Fatty atrophy was observed after THR contributing to functional outcome deterioration [37].…”
Section: Discussionmentioning
confidence: 98%
“…Wu et al [20] believed that the recovery of the gluteus medius' strength and the balance of soft tissue around the hip were very important, which could affect the outcoming of THA. Damm P et al [21]. also recognized the importance of the gluteus medius muscle and believed that the situation of gluteus medius muscle strength should be fully considered before and after surgery, otherwise, the surgical efficacy would be affected.…”
Section: The Impact Of Restoring Hip Rotation Center On the Functionamentioning
confidence: 99%
“…Es konnte ferner gezeigt werden, dass sich nach 20-minütigem langsamen Gehen bei 2,5 km/h die Gelenkkräfte nicht verändern [9]. Unstimmigkeiten zwischen den Messungen, insbesondere zwischen [7] und [9], lassen sich darauf zurückführen, dass die Dysfunktion eines Muskels die Gelenkskontaktkraft erhöht (Impaired gait), weil ein Teil des erforderlichen Gelenksmoments durch andere Muskeln kompensiert werden muss, die unvorteilhaft kurze Hebelarme besitzen und hierdurch höhere Gelenkskräfte erzeugen [10,11]. Während bis hier lediglich die resultierende Gelenkskraft und wegen des steilen Einfallswinkels damit quasi die kompressive Kraftkomponente im Sinne der Belastung beachtet wurde, wurden in den Untersuchungen auch andere strukturelle Beanspruchungen, wie Biege-und Torsionsmomente gemessen.…”
Section: Was Ist Zu Diesem Thema Bereits Bek Annt?unclassified
“…Die effektive Pufferwirkung der Muskulatur kann auch darin gesehen werden, dass es innerhalb der Bewegungsklassen zu vergleichbaren Belastungen kommt. Ist die Funktion eines Muskels allerdings gestört, kommt es konsequenterweise zu einem entsprechenden Belastungsanstieg, wie am Beispiel des M. Glutaeus minimus beobachtet werden konnte [11]. Diese Ergebnisse unterstreichen den hohen Wert eines kombinierten Kraft-und Sensomotoriktrainings in der Rehabilitation und Prävention.…”
Section: Diskussion Und Relevanz Für Die Praxisunclassified